OH FULL-FLEDGED ISLAMIC BANKS! DO YOU DISCLOSED YOUR PRODUCT DISCLOSURE SHEET? - Muhammad Fakhirin Bin Che Majid; Assoc. Prof. Dr. Muhammad Nasri Bin Md. Hussain; Dr. Suhaimi Bin Ishak (International Journal of Accounting, Finance and Business, 2020)
Product Disclosure Sheet (PDS) caught low level of awareness by the consumers regarding the availability to obtain product information and facilitate them in financial decision making. PDS of banking product is crucial and needed by the consumer according to the five disclosure principles which are timely, clear and concise, accurate and relevant, highlight important information, and consistent and comparable. The objective of the paper is to highlight the practice of disclosing the PDS by local owned full-fledged Islamic banks in Malaysia. The study is quantitative research and data were collected from the banks’ website. The data was analysed using SPSS. Findings revealed that all Islamic banks make the product disclosure sheet available in their website, however, there are banks which did not disclosed the PDS for a few of their Islamic home financing products which is BIMB and BMMB. It is highly recommended for the Islamic banks to deliver such information in promoting best practices when providing services to customer without ambiguity. Survey of disclosure practice and quality of PDS could be conducted in the area of all Islamic banks for future study to compare the practice.